Endothelial Cell-Derived Extracellular Vesicles Target TLR4 via miRNA-326-3p to Regulate Skin Fibroblasts Senescence - Xinni Yang; Jiyong Tan; Jiqing Shen; Xin Zhang; Gaoxiang Huang; Xiaoxue Su; Jing Li (Journal of Immunology Research)
Backgrounds. Skin aging could be regulated by the aberrant expression of microRNAs. In this manuscript, we explain that endothelial cell-derived extracellular vesicles could act as supporters to deliver exogenous miR-326-3p to accelerate skin fibroblasts senescence. Methods. β-galactosidase senescence staining assay, Hoechst 33258 apoptosis staining assay, and Ki67 staining assay were used to evaluate the biological function of mouse skin fibroblasts. Real-time PCR was applied to assay miRNAs and mRNAs expressions. Western blot was used to detect TLR4 protein expression. The target gene of miRNA were identified using a double luciferase reporter assay. miR-326-3p mimic/inhibitor and siRNA-TLR4 can demonstrate a nonnegligible link between miR-326-3p-TLR4 and skin aging. Results. In coculture experiment, senescence endothelial cells could promote the skin fibroblasts senescence and apoptosis via extracellular vesicles pathway. In contrast, miR-326-3p mimics accelerated senescence and apoptosis of skin fibroblasts, while miR-326-3p inhibitor could dramatically delay skin fibroblasts senescence and apoptosis. TLR4 was proved to be a miR-326-3p directly target gene via double luciferase assay. After skin fibroblasts transfected with siRNA-TLR4, cellular senescence and apoptosis were significantly increased. Furthermore, the skin tissues of aging mice were shown with overexpression of miR-326-3p and decrease of TLR4 gene and protein expression levels. Conclusions. Endothelial cell-derived extracellular vesicles delivery of miR-326-3p was found to have a function in skin fibroblasts via target TLR4. Therefore, endothelial cell-derived extracellular vesicles in antiaging therapies might be a new treatment way for delaying skin aging.